The influence of patients age, type of tumor growth, hematocrit, and radiation-induced tumor regression on the prognosis of advanced uterine cervix carcinoma - Boljesíková, E; Gyárfásová, M; Durkovský, J (Neoplasma, 1988)
The age of patients, type of tumor growth, pretreatment hematocrit, and radiation-induced tumor regression were evaluated as possible prognostic factors in 222 patients with advanced cervical cancer treated at the Institute of Clinical Oncology in Bratislava in the period from 1960 through 1980. The five-year disease-free survival rate for Stage IIb patients was 50%, for Stage III patients 23.1%, and for Stage IV patients 13%. Radiation-induced tumor regression and type of tumor growth were noted to be a significant prognostic factor with regard to the control of disease in the pelvis. Age of the patients and pretreatment hematocrit were found to be a weak prognostic factor.
Keywords: Prognosis; Humans; staging nádorů; následné studie; lidé středního věku; Neoplasm Staging; Middle Aged; pojišťovací analýza; hematokrit; Carcinoma, Squamous Cell; prognóza; Follow-Up Studies; Actuarial Analysis; Age Factors; spinocelulární karcinom; Adenocarcinoma; nádory děložního čípku; Uterine Cervical Neoplasms; ženské pohlaví; věkové faktory; Hematocrit; lidé; adenokarcinom; Female